Gabriel Trujillo Muñoz: Writer, Editor and Researcher of Mexican Science Fiction - Manickam, Samuel (2014)
Gabriel Trujillo Muñoz is one of the most important figures in contemporary Mexican science fiction. For more than thirty years this author and scholar from Mexicali has raised the visibility of this literary genre in Mexico through stories, novels, anthologies and critical studies. This article provides a panoramic overview of this author’s most relevant works, from his stories to his monographs.